The protection of women from cyber blackmail in Arab countries in the light of International Human Rights Law - Elshobake, Mohammed R. M. (2023)
Cyber blackmail is an increasingly common form of crime around the world. However, it has become particularly prevalent in Arab countries such as Egypt, Iraq, Lebanon, Syria, Morocco, Jordan, Palestine, and other Arab countries, where women are often targeted. Cyber blackmail involves threatening to release sensitive or damaging information about a victim unless they comply with the perpetrator's demands. In the case of women, this often involves sexual content or personal information that could lead to social or cultural shame. This paper seeks to provide a comprehensive concept of the crime of cyber blackmail. It focuses on the prevalence and forms of cyber blackmail in Arab Countries, and reasons for the prevalence of cyber blackmail crimes against women in Arab countries. This paper will highlight the impact of cyber blackmail on women's lives in Arab Countries. Additionally, it aims to present a promising initiative to protect women from cyber blackmail in Arab countries. This paper will mainly use descriptive and analytical research to examine the main issues of cyber blackmail against women in Arab countries in the light of International Human Rights Law. It is concluded that there are several factors for the prevalence of blackmail against women in Arab countries, including the increase in the number of Internet and social media users, the cultural and social factors represented in the fear of scandal, the lack of awareness of the victim and her family, and the deterioration of economic conditions, the political problems that many Arab countries suffer from, weakness of legal protection, weakness of capabilities and complexity of procedures. Finally, this paper suggested a promising initiative that could effectively combat cyber blackmail against women in Arab countries.